Intellectual property and developing countries a review of the literature - Hassan, Emmanuel; Yaqub, Ohid; Diepeveen, Stephanie (RAND, 2010)
"This report examines the impact of intellectual property rights in developing countries, in the context of the World Trade Organization's Agreement on Trade-Related Intellectual Property Rights (TRIPS) and the development of TRIPS-plus standards."--Website